2013
DOI: 10.1597/11-143
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience in a Sample of Adolescents and Young Adults with Cleft Lip and Palate in Brazil

Abstract: Objective : To compare the caries experience of adolescents and young adults with cleft lip and/or palate (CL/P) with a noncleft control group. Design : Thirty CL/P subjects and 30 controls were clinically examined to obtain the decayed, missing and filled teeth (DMFT) and the decayed, missing and filled surfaces (DMFS) indices, gingival bleeding index, plaque index, and active caries lesions. Data concerning oral hygiene, access to fluoridated water, mother's education level, and family income were also colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 26 publications
0
52
0
4
Order By: Relevance
“…Following exclusion on the basis of the content of the abstract, 14 articles were evaluated in their full-text form. Strict application of the inclusion and exclusion criteria provided 7 studies [Lucas et al, 2000;AlWahadni et al, 2005;Mutarai et al, 2008;Al-Dajani, 2009;Hazza'a et al, 2011;Freitas et al, 2012;King et al, 2012] that were included in the present meta-analysis ( fig. 1 ).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following exclusion on the basis of the content of the abstract, 14 articles were evaluated in their full-text form. Strict application of the inclusion and exclusion criteria provided 7 studies [Lucas et al, 2000;AlWahadni et al, 2005;Mutarai et al, 2008;Al-Dajani, 2009;Hazza'a et al, 2011;Freitas et al, 2012;King et al, 2012] that were included in the present meta-analysis ( fig. 1 ).…”
Section: Study Selectionmentioning
confidence: 99%
“…The reporting of information in individual studies was not always complete. For example, one study [Al-Dajani, 2009] did not report on the exact types of CLP of the patient sample, the number of examiners, or error of the method measurements, while another study [Freitas et al, 2012] did not report on the specific caries diagnostic criteria used.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…10,19,20 Sixteen studies were reported from 1999 to 2017 on the prevalence of dental caries in CLP individuals (Table 2), differing on the study type (systematic reviews and meta-analysis, narrative reviews, cross-sectional, retrospective, descriptive and case-control), geographic area, sample size and measured plaque indexes. 6,12,23,35,38 This was observed in patients in different phases of oral development, and it was similar in the primary, mixed and permanent dentitions, suggesting that the increased risk of oral problems persists. Several studies showed that this prevalence was higher compared to common matched individuals, 5,9,21 and two articles presented evidence of differences by cleft type (CL<CLP or CP) on the caries prevalence.…”
Section: Discussionmentioning
confidence: 90%
“…Fourteen studies, including an epidemiological survey, and cross-sectional, case-control, prospective and observational studies, showed the same pattern compared to those that analysed these parameters separately. 16,35 The use of fluoride products was reported in a variety of studies, [4][5][6]8,12,16,21,29,34 and some of them showed that this was higher in CLP patients than in controls. 6,12,23,35,38 This was observed in patients in different phases of oral development, and it was similar in the primary, mixed and permanent dentitions, suggesting that the increased risk of oral problems persists.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, fibrose do lábio e presença de bridas na região anterior, consequência das cirurgias primárias, são bastante comuns (FREITAS et al, 2012b;ANTONARAKIS;PALASKA;HERZOG, 2013). Todos estes fatores podem ser coadjuvantes no risco à doença cárie, por favorecerem um maior acúmulo de biofilme (PARAPANISIOU et al, 2009;ZHU et al, 2010;KING;WONG;WONG, 2013 Especificamente na população brasileira, um estudo recente encontrou maior prevalência de cárie dentária em uma amostra de indivíduos adolescentes e adultos jovens com fissura labiopalatina comparada com indivíduos sem fissura (FREITAS et al, 2013), enquanto outro estudo não encontrou diferença estatisticamente significativa entre os índices CPOD no grupo com fissura (1,20) e sem fissura (0,90) em uma amostra de crianças e adolescentes com fissura labiopalatina (TANNURE et al, 2012 O uso da sonda exploradora deve ser abandonado devido ao grande risco de promover dano estrutural ao esmalte desmineralizado durante o procedimento de sondagem e ao fato de que seu uso não traz benefícios para a acurácia do diagnóstico das lesões de cárie, sendo recomendado o uso de uma sonda OMS (com extremo arredondado) especialmente durante a verificação da integridade e rugosidade da superfície (MANTON, 2013).…”
Section: Lista De Figurasunclassified